Didascalia cioè dottrina comica libri tre (1658-1661) Saggio introduttivo. L'opera esemplare di un 'moderato riformatore', edizione critica e note di Sandro Piazzesi - Bartolomei, Girolamo (Moderna/Comparata, 2016)
Girolamo Bartolommei's literary research is characterised by the narration of actions carried out by sacred and profane subjects and by the narration of ancient fabulae, re-interpreted according to the principle of moral utility. Girolamo Bartolommei dealt with different forms of lyrical, epic, dramaturgical and musical writing, recalling 'the benign readers' of his works to the ethical and social function of poetry. His work Didascalia cioè dottrina comica ("Caption, that is comic doctrine" printed in Florence in 1658 and reprinted in 1661), of which the critical edition is here introduced, is of particular interest for the peculiarity of the theoretical proposal. Such proposal is ascribable to the aesthetic of the academy theatre, aimed at demonstrating to young writers that only the 'honesty' and the decorum of a 'well-ordered comedy' could lift the fate of comic art from the degradation in which it had fallen. The author tries to convey this idea by proceeding from questions of general poetics up to the 'sketches of middle comedies' he composed himself.